Incentive design and trust: comparing the effects of tournament and team-based incentives on trust - Robert J. Oxoby; Colette Friedrich (Institute for the Study of Labor (IZA), 2008)
We explore the extent to which the structure of incentives affects trust. We hypothesize that the degree to which different incentive mechanisms emphasize competition (via the perceived intentions of others) and entitlements (via the perceived property rights) will affect individuals' subsequent behavior. In our experiment, bargaining pairs earned endowments through either tournaments or team-based incentives. Participants engaged in a subsequent trust game in which the sender had access to the total endowment generated by the pair. We find that the structure of the incentive mechanisms has asymmetric effects on observed trust in which participants' relative performance framed trusting behavior.
urn:nbn:de:101:1-2008040197
Keywords: J31; 330; Trust; incentives; experiments; tournaments; Extensives Spiel; Gruppenarbeit; Vertrauen; Ökonomischer Anreiz; Test; Theorie